Nanotechnology-Based Delivery Systems for Antimicrobial Peptides - Adewale Oluwaseun Fadaka; Nicole Remaliah Samantha Sibuyi; Abram Madimabe Madiehe; Mervin Meyer (MDPI AG, 2021)
Antimicrobial resistance (AMR) is a significant threat to global health. The conventional antibiotic pool has been depleted, forcing the investigation of novel and alternative antimicrobial strategies. Antimicrobial peptides (AMPs) have shown potential as alternative diagnostic and therapeutic agents in biomedical applications. To date, over 3000 AMPs have been identified, but only a fraction of these have been approved for clinical trials. Their clinical applications are limited to topical application due to their systemic toxicity, susceptibility to protease degradation, short half-life, and rapid renal clearance. To circumvent these challenges and improve AMP's efficacy, different approaches such as peptide chemical modifications and the development of AMP delivery systems have been employed. Nanomaterials have been shown to improve the activity of antimicrobial drugs by providing support and synergistic effect against pathogenic microbes. This paper describes the role of nanotechnology in the targeted delivery of AMPs, and some of the nano-based delivery strategies for AMPs are discussed with a clear focus on metallic nanoparticle (MNP) formulations.